Rapamycin relieves inflammation of experimental autoimmune encephalomyelitis by altering the balance of Treg/Th17 in a mouse model. (13th July 2019) - Li, Zhenfei; Nie, lingling; Chen, Liping; Sun, Yafei; Li, Guo
Highlights: Rapamycin attenuated the infiltration of inflammatory IL-17 cells in EAE via mTOR signaling pathway. The percentage of Treg cells in CD4+ cells significantly increased with high-dose rapamycin. Rapamycin, via an immunomodulatory mechanism, can be suggested for the treatment of multiple sclerosis. Abstract: This study was to observed the different doses of rapamycin on the treatment of experimental autoimmune encephalomyelitis (EAE) in C57BL/6 mice. 63 female C57BL/6 mice (6–8 weeks) was chosen and randomly divided into three groups: control, low-dose rapamycin-treated EAE mice (0.3 mg/kg), and high-dose rapamycin-treated EAE mice (1 mg/kg). The EAE mice recovery of neurological function in different concentrations of rapamycin were assessed by neurological function score; The assessment of neurological function was divided into three periods: initial stage (10-13d), peak phase (17-21d), remission phase (25-28d), and calculated the score for each period. The inflammatory cell infiltration of mice was assessed by IL-17 A immunohistochemical staining which produced by Th17 cell and positive cell count. The autoimmune recovery of EAE mice was evaluated by flow cytometry on the expression of CD4+ CD25+ Foxp3+ T cells. The transcription factors of Foxp3+ and RORC (RAR-related orphan receptor C) mRNA expression were evaluated by qRT-PCR in Treg cells and Th17 cells. In the neurological function score, the high-dose group was significantly lower than the other two groups in the peak drug phase and the remission phase (P < 0.05), while there was no significant difference in the initial stage (P > 0.05). The percentage of CD4+CD25+Foxp3+T cells, the number of Th17 cells, and the expression of Foxp3 and RORC mRNA level in the high-dose rapamycin group were greater than those in the vehicle-treated group and the low-dose rapamycin group. High doses of rapamycin (1 mg/kg) have a better relieves inflammation of EAE by altering the balance of Treg/Th17 in a mouse model.